Proposed Method to Increase Productivity at PT AMI - Andhella, Arief; Wibisono, Dermawan (The Indonesian Journal of Business Administration, 2013)
PT AMI is a bakeware manufacture located in Bandung and all its product is 100 percent export oriented. The products are exported to American and European markets. The type of business is based on jobs order or customers’ orders. The company found that low productivity and high number of defects have caused the company to lose sales and profits. During the analysis the main problem regarding quantity lies in the Unit Press Shop, which has poor layout which causing the production unable to reach optimum level. While in the quality issue, the problem lies in the Unit Press Shop and Unit Painting. The problems are due to lack of knowledge of the operators. The methods that will be discussed in analyzing the roots of problems in PT AMI are the Lean Manufacturing concept with DMAIC methodology to identify the root of the caused and waste in the manufacturing area. The propose method in order to eliminate the problems are additional machines, new layout and the grouping of similar items and processes help to improve the capacity in production. The capacity improvement is about 85.5% compare to the existing system. Another proposes solution is to create training for the operators to improve the skill and knowledge regarding the impact of high reject to the company’s growth. The first expectation after the training is the improvement of 20% compare to total reject in 2012. The implementation to improve the productivity will require the effort and team works form few departments. The timeline in applying the propose methods will takes about three months starting from January 2014.Keywords: Lean manufacturing, productivity and optimum management.